2022
DOI: 10.12965/jer.2244484.242
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal and lower extremity muscles activity and thickness in typically developing children and children with developmental delay

Abstract: We investigated abdominal and lower extremity muscle activity and thickness in typically developing children and children with developmental delays. A total of 35 children participated: typically developing peers (n = 13), children with hypotonia (n = 10), and children with spasticity (n = 12). Muscle activity and thickness were measured at rest and during activity. Electromyography was used to measure abdominal and lower extremity muscle activities, and abdominal muscle thickness was measured using ultrasonog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In this study, it is thought that DD children with hypertonia made movements through compensation because the base of support was narrow during STS, making it difficult to control RA effectively. DD children with hypotonia and TD children show similar abdominal muscle contraction ( Ha and Sung, 2022 ). Peredo and Hannibal (2009) reported that DD children with hypotonia exhibit mild muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it is thought that DD children with hypertonia made movements through compensation because the base of support was narrow during STS, making it difficult to control RA effectively. DD children with hypotonia and TD children show similar abdominal muscle contraction ( Ha and Sung, 2022 ). Peredo and Hannibal (2009) reported that DD children with hypotonia exhibit mild muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic predisposition, coupled with acquired risk factors, can accelerate ventricular enlargement. Primary hydrocephalus can also stem from developmental disorders linked to central nervous system birth defects, such as neural tube defects, arachnoid cysts, Dandy-Walker syndrome, and Chiari malformations [8,9]. Developmental delay is typically identified when a child fails to achieve developmental milestones at the anticipated times in comparison to their peers [10], indicating a delay in any dimension of functioning at the expected age [11].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic predisposition, coupled with acquired risk factors, can accelerate ventricular enlargement. Primary hydrocephalus can also stem from developmental disorders linked to central nervous system birth defects, such as neural tube defects, arachnoid cysts, Dandy-Walker syndrome, and Chiari malformations [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%